Some comments to the tax consequences arising from cross-border secondment of staff - López Saldaña, Cesar (2016)
The objective of this article is to analyze, from a tax perspective some aspects arising from the secondment, such as the possible double residence of the employees assigned, the application of income tax on income from personal servicedependent on light model Convention for the Avoidance of Double Taxation of the Organization for Economic Cooperation and Development (“OECD CDI”) and the possible establishment of a permanent establishment by assigning employees to the State of destination.